Churchill's "Iron Curtain" speech fifty years later - Muller, James W., 1953-; Churchill Center, Washington, D.C. (Columbia : University of Missouri Press, 1999)
"Winston Churchill's visit to Fulton, Missouri, on March 5, 1946, marked the first public recognition of the cold war that was to follow World War II. Churchill delivered his most famous speech, "The Sinews of Peace," which became best known by the phrase he used to describe the cold-war division of Europe, the "iron curtain.""--Jacket
"The "Iron Curtain" speech defined postwar relations with the Soviet Union for citizens of Western democracies. Although it initially provoked intense controversy in the United States and Britain, criticism soon gave way to wide public agreement to oppose Soviet imperialism."--Jacket
"Opening with the full text of the address Churchill delivered in Fulton and concluding with Margaret Thatcher's fiftieth-anniversary address surveying the challenges facing Western democracies in this post-cold war climate, the book brings together essays that reflect on the past fifty years, recognizing Churchill's speech as a carefully conceived herald of the cold war for the Western democracies
These powerful essays offer a fresh appreciation of the speech's political, historical, diplomatic, and rhetorical significance."--Jacket
Mr. Churchill goes to Fulton / John Ramsden -- The beginning of the Cold War / Paul A. Rahe -- Moral principle and realistic judgment / Daniel J. Mahoney -- A philosophy of international politics / Spencer Warren -- True politics and strategy / Larry P. Arnn -- Rhetorical statesmanship / Patrick J.C. Powers -- Epilogue: new threats for old / Margaret Thatcher -- Contributors and credits -- Index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Churchill, Winston, -- 1874-1965.; Sinews of peace (Churchill, Winston); Churchill, Winston, -- 1874-1965.; Churchill, Winston, -- 1874-1965; World politics -- 1945-1989.; Politique mondiale -- 1945-1989.; HISTORY -- Modern; World politics; Koude Oorlog; Redes; World politics -- 1945-; 1945-1989